O valor percebido pelo cliente no mercado de telefonia móvel empresarial: o caso de uma operadora em Curitiba/PR - Santos, Cristian Bettoni (2018)
The objective of this monograph was to define which are the parameters and the preponderant factors involved in the choice of the mobile operator, taking into account the expectations of the consumer and the reality of the services offered. The research had as main argument the understanding of value added through the decision criteria in the choice of the mobile phone company by the user. In order to do só, two questionnaires were used: one on Customer Expectation and the other on “Customer Reality”, with a survey of 100 different companies using the services of the “W” operator, located in the city of Curitiba / PR, “. As a result, it was possible to highlight the determining factors in the choice and maintenance of the service offered by a mobile operator. It was identified that customer satisfaction is paramount for the maintenance of the same. The companies cannot convince unhappy customers to stay with them. Therefore, it can be concluded that, mobile service providers need to continually monitor the market in order to ensure that their offerings, rates, signal coverage and quality of services are better than those of their competitors, making their customers with their needs met and satisfied with the contracted provider.